Các đồng bằng châu Á: Từ nguy cơ đến phục hồi (Asian Mega-Deltas: From risk to resilience) - International Rice Research Institute (International Rice Research Institute, 2022)
Vietnamese translation of the brief introducing the CGIAR Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience (AMD), its focus research areas, and target outcomes.